(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Electromagnetic radiation is the leading cause of diseases in some special environments. With the development of functional clothing design, simulation technology have been increasingly emphasized. Understanding the electromagnetic radiation protective mechanism through a FEA Bionelectromagnetic model is of great significance for male’s reproductive system protection. This 3D FEA Bionelectromagnetic model includes muscle model, pelvic model, thigh bone model, bladder model, prostate model, and testis model. The influence of silver layer and bronze layer on electromagnetic field shielding within a dressed manikin exposed to 915 MHz were investigated. Simulated results indicated that testis were protected mostly by electromagnetic radiation protective underwear and other tissues have received various degrees of damage. Increasing the fabric thickness was an effective method to reduce the electromagnetic radiation energy. Therefore, it is important to develop a bioelectromagnetic model to research the shielding effectiveness of the product. Taking the value of electric field strength, magnetic strength and SAR to evaluate influence from radiation source. The bioelectromagnetic model could help designers to forecast the performance of electromagnetic radiation protective underwear, and the results provide the basis for optimum design.